THE IMPLEMENTATION OF TEMBANG MACAPAT’S VALUES IN THE SAMIN COMMUNITY’S LIFE - Rusmawati, Roosi; Khasanah, Ismatul; Mauliddian, Khilmi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
This study describes the macapat song tradition of the Samin people in Bojonegoro. Samin is a community that has a unique culture, one of which is the macapat song tradition. This tradition is one of the cultural representations of the local community. In exploring the values of this tradition, this study uses the folklore theory. Folklore is closely related to the condition of society and the culture that surrounds it, so it is necessary to understand and give meaning to folklore. The method in this research is qualitative. Data were collected by interviewing respondents, observing and documenting the macapat song tradition in the Samin community. There are three macapat songs on Samin's teachings. The songs are of the Dandang Gula, Pangkur, and Pucung. As for the three values, the first contains the values based on the Dandang Gula song, which contains rules for maintaining the behavior of fellow humans and nature, the second is the value based on the Pangkur song, namely about marriage and family relationships, and the third is the value based on the Pucung song regarding the guidelines for human life.